Efek Aktivitas Masyarakat Terhadap Kelimpahan Ikan Garing (Tor tambra) di Sungai Batang Gadis Kabupaten Mandailing Natal Sumatera Utara - Nisa Hidayati; Yunasfi Djayus; Riri Ezraneti (Program Studi Manajemen Sumberdaya Perairan, Fakultas Pertanian Universitas Sumatera Utara, 2015)
Garing fish is fresh water fish living the river stream.Beside fish living in the river where the water is not pollution. Garing fish so the fish species very speciality in Mandailing Natal region. Fish species Garing fish habitat in Batang Gadis river very influential the fisic and chemical water. Garing Fish is depent of temperature for overflowing of fish. Has been analyzed in March-April 2014 in Batang Gadis river. Sample Identification from four location with three examination. In order to determination sample location is using “Purpossive Random Sampling” and sample analyzed water quality. The result of research in Batang Gadis river have been found one clas from ordo cypriniformes is for about 59 . The Highest population fishes density Garing fish with grade 0,0007 perm², meanwhile the lowest population fish density Garing fish is for about 0,0001 perm². Fish type with the highest presentation is Garing fish for about 50%, meanwhile the lowest is for about 16,6%. The overflowing fish with the highes presentation is Garing fish for about 18,5% and meawhile the lowest is for about 2,0%.Key word : The overflowing fish, Tor tambra, Batang Gadis